"It's Time You Knew: I'm a Contemporary, Too … ". (2nd October 2018) - Aizenberg, Mikhail
Abstract : This first part of a two-part publication holds four presentations from a roundtable on the poetry and continuing influence of Osip Mandelstam (1891-1938), with presentations by Mikhail Aizenberg, Vladimir Aristov, Leonid Vidgof and Konstantin Komarov. Aizenberg discusses the rising reputation of Mandelstam in the last three decades of the Soviet era; Aristov raises "problems and lessons" of Mandelstam, often in a transnational literary context; Vidgof addresses what makes Mandelstam "contemporary" to this day, particularly as a Jewish poet; Komarov briefly considers the "dreadful providentialism" of Mandelstam's writing and the connections of his work to poets who are writing now.